Q: What is an equation using five 2's that equals 34?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Points: (s, 2s) and (3s, 8s) Slope: (8s-2s)/(3s-s) = 6s/2s = 3 Perpendicular slope: -1/3 Midpoint: (s+3s)/2 and (2s+8s)/2 = (2s, 5s) Equation: y-5s = -1/3(x-2s) => 3y-15s = -1(x-2s) => 3y = -x+17x Perpendicular bisector equation in its general form: x+3y-17s = 0

17

5s - 6 = 2s, ie 5s - 2s = 6, ie 3s = 6, ie s = 2

You said that 4(2s - 1) = 7s + 12Eliminate parentheses: 8s - 4 = 7s + 12Add 4 to each side: 8s = 7s + 16Subtract 7s from each side: s = 16

2s-2b= a+b+c-2b simplified that would be a+c-b.

Related questions

(22/2+2)x2

It is a simple linear equation in 's'. Its solution is the number that 's' must bein order to make it a true statement. The solution may be found like this:4s + 10 = 2s + 2Subtract 10 from each side of the equation:4s = 2s - 8Subtract 2s from each side:2s = -8Divide each side by 2 :s = -4

22 + 22 - 2 = 42

2s + 17 = 2s + 17 1) First, you want to start on the left side of the equation and subtract 17 from both sides. 2s = 2s 2) Then, you take the 2 on the left side and divide it on both sides. s = s 3) You are left with s (Or 1s) on both sides, so s = 1.

2r + 2s = 50 2r - s = 17 therefore 4r - 2s = 34 Add so that you can eliminate one of the variables: 2r + 2s = 50 4r - 2s = 34 ---------------- 6r + 0s = 84 Solve for r: 6r = 84 r = 14 Substitute r into one of the original equations: 2(14) + 2s = 50 28 + 2s = 50 2s = 22 s = 11 Doublecheck with the other original equation: 2(14) - 11 = 28 - 11 = 17

2s + s + 12 = 132 3s + 12 = 132 3s = 132 - 12 3s = 120 s = 40

Points: (s, 2s) and (3s, 8s) Slope: (8s-2s)/(3s-s) = 6s/2s = 3 Perpendicular slope: -1/3 Midpoint: (s+3s)/2 and (2s+8s)/2 = (2s, 5s) Equation: y-5s = -1/3(x-2s) => 3y-15s = -1(x-2s) => 3y = -x+17x Perpendicular bisector equation in its general form: x+3y-17s = 0

It can't be solved because it's not an equation.

17

2s - 12 + 2s = 4s - 124s - 12 = 4s - 124s = 4ss = s==========this is an identity and any number can be s

5s - 6 = 2s, ie 5s - 2s = 6, ie 3s = 6, ie s = 2

You said that 4(2s - 1) = 7s + 12Eliminate parentheses: 8s - 4 = 7s + 12Add 4 to each side: 8s = 7s + 16Subtract 7s from each side: s = 16